1995
DOI: 10.1111/j.1365-2621.1995.tb06272.x
|View full text |Cite
|
Sign up to set email alerts
|

Color Stability and Microbial Growth Relationships in Beef as Affected by Endogenous α‐Tocopherol

Abstract: Longissimus muscle from Holstein steers supplemented with vitamin E at 500 or 2000 mg/head/day showed less surface metmyoglobin accumulation than controls during 12 days storage at 4°C. Temperature abuse at 25°C for 24 hr increased metmyoglobin formation; vitamin E supplementation diminished the adverse effect of temperature abuse. No differences (P > 0.05) in bacterial load were observed among the 3 vitamin E treatments during storage. Sensory panelists preferred vitamin E-supplemented beef steaks in visual a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
21
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 16 publications
(23 reference statements)
6
21
0
Order By: Relevance
“…In experiment 2, vitamin E supplementation did not influence the bacterial load. These results correspond with data from Chan et al (1995) and Zerby et al (1999). Table 7 shows that the microbial counts of the samples of day 0 were already above legal limits (>10 3 cfu g -1…”
Section: Vitamin E Concentrationssupporting
confidence: 72%
See 1 more Smart Citation
“…In experiment 2, vitamin E supplementation did not influence the bacterial load. These results correspond with data from Chan et al (1995) and Zerby et al (1999). Table 7 shows that the microbial counts of the samples of day 0 were already above legal limits (>10 3 cfu g -1…”
Section: Vitamin E Concentrationssupporting
confidence: 72%
“…The rate of discolouration of meat is related to the effectiveness of oxidation processes and enzymatic reducing systems in controlling metmyoglobin levels in meat (Chan et al, 1995). There were no differences in colour measurements for L*, a* or b* values (Table 5).…”
Section: Vitamin E Concentrationsmentioning
confidence: 85%
“…The a* colour coordinates (green to red) have been highly correlated with panel assessment of discolouration (Chan et al 1995) in trials with dietary vitamin E. In the present study, increased colour case life attributable to vitamin E had no effect on the microbial condition (Chan et al 1996). It has also been well documented that supplemental vitamin E delays metmyoglobin accumulation during the display of a number of beef cuts following limited periods of storage (1 to 3 wk) in vacuum (Faustman et al 1989b;Arnold et al 1993b;Mitsumoto et al 1994).…”
Section: Discussionsupporting
confidence: 49%
“…These beneficial effects are without impact upon the growth of meatborne pathogens or spoilage bacteria (Chan et al 1994;Smith et al 1994). More recent studies by Chan et al (1995Chan et al ( , 1996 showed that elevated α-tocopherol did not mask bacterial spoilage.…”
mentioning
confidence: 99%
“…Some authors observed improved colour stability when vitamin E was added (e.g. Faustman et al, 1989;Chan et al, 1995;Lavalle et al, 1995;Vega et al, 1996). The antioxidant may prevent oxidation of myoglobin to metmyoglobin and improve membrane stability (Williams et al, 1992;Arnold et al, 1993;Buckley et al, 1995).…”
Section: Resultsmentioning
confidence: 99%